Economic impact of bridge functionality loss from a resilience perspective: Queensferry Crossing, UK. Issue 4 (29th December 2021) - Smith, Alec W.; Argyroudis, Sotirios A.; Winter, Mike G.; Mitoulis, Stergios A.
Abstract : Understanding the resilience of transport networks is critical for efficient asset management. This paper takes an innovative approach to studying the operability of the Queensferry Crossing (QFC), UK, including cost–benefit aspects. A key driver for the QFC was to increase the resilience of the A90/M90 link by reducing weather-related closures. The first weather-related closure of the QFC was in February 2020, when ice formed on the superstructure cables and fell on the carriageway and vehicles, creating a safety risk for bridge users. The bridge was closed for 41 h and, in this paper, the estimated monetary losses are compared with those of past Forth Road Bridge (FRB) closures. The costs of potential mitigation measures are then assessed in the context of closure costs, thus improving the resilience of the QFC. Although the QFC has only been open for 3 years, it is already apparent that it is significantly more resilient than the largely replaced FRB, whether this is considered as the number, duration or costs of closures and that this will be substantially improved by the planned use of the FRB during future closures of the QFC. Investment in mitigation measures is a potentially cost-effective solution although the form of any suitable ice prevention or removal system is, as yet, far from clear.